Attributes of industry, industry segment and firm‐specific information in security valuation* - TSE, SENYO (Contemporary Accounting Research, 1989)
Abstract. One of the objectives of segment reporting, as expressed in the FASB's Statement of Financial Accounting Standards Number 14, is to enable investors to improve their assessments of companies' opportunities for future growth. Implicit in this idea are the assumptions that (1) industry membership provides information on companies' growth prospects, and (2) segment data provide incremental information over consolidated data for assessing industry‐related growth prospects. This research examines these assumptions by using an informational perspective for earnings. The informational perspective on accounting information posits that a role of accounting data such as earnings is to alter investors' beliefs about a company's future dividend paying ability, as reflected in its prospective cash flows. Specifically, this study shows that the relationship between earnings amounts and current security prices depends on whether the earnings originate from high growth or low growth industries, as defined in the paper. Furthermore, segment data appear to improve the informativeness of such an earnings classification for explaining security prices. The results suggest that investors use information on industry growth prospects in analyzing individual companies, and that segment information plays a useful role in improving such analyses. Résumé. L'un des objectifs de l'information sectorielle, tel qu'il est exprimé dans le Statement of Financial Accounting Standards No. 14 du FASB, est de permettre aux investisseurs d'évaluer avec plus de précision le potentiel de croissance des entreprises. Certaines hypothèses sont implicites à cet objectif: 1) l'appartenance au secteur donne accès à de l'information sur les perspectives de croissance des entreprises et 2) les données sectorielles offrent un supplément d'information, par rapport aux données consolidées, dans l'évaluation des perspectives de croissance liées au secteur. L'auteur examine ces hypothèses dans l'optique du contenu informationnel des bénéfices. Cette optique sur l'information comptable établit le principe selon lequel l'un des rôles de données comptables telles que les bénéfices consiste à modifier les convictions des investisseurs au sujet du potentiel de l'entreprise en termes de dividendes, tel que le reflètent ses flux monétaires éventuels. L'étude démontre précisément que la relation entre le montant des bénéfices et le cours des titres dépend du fait que les bénéfices proviennent de secteurs à forte ou à faible croissance, selon la définition du texte. De plus, les données sectorielles semblent améliorer le pouvoir explicatif de cette classification des bénéfices quant au cours des titres. Les résultats obtenus laissent supposer que les investisseurs utilisent l'information sur les perspectives de croissance du secteur dans l'analyse des différentes sociétés, et que cette information sectorielle joue un rôle appréciable dans l'amélioration de ce genre d'analyse.